Land use and land cover change detection and prediction in Bhutan's high altitude city of Thimphu, using cellular automata and Markov chain - Sonam Wangyel Wang (Environmental Challenges, 2021)
Rapid urbanization is changing landscapes often resulting in the degradation of ecosystem services and quality of urban life. Remote sensing and GIS tools can provide valuable information to deepen our understanding of the dynamics of these changes to better plan and build sustainable cities for the future. Using remote sensing data, socio-economic data, and field observations, we simulated spatiotemporal dynamics of land use and land cover changes in the city of Thimphu. Simulation results reveal that the landscape of Thimphu city has changed considerably during the study period and the change trend is predicted to continue into 2050. The study observed a significant increase (12.77%) in built-up area from 2002 (52.88%) to 2018 (65.5%), followed by a slight increase in the cover of bare ground. On the contrary, forest cover declined drastically (15.25%) followed by agriculture (1.01%). Rapid population growth triggered by rural urban migration coupled with hasty socio-economic development post democracy are the main drivers of these changes. These changes have fragmentated forest cover, increased soil/gully erosion, surface runoff, and storm induced floods of storm and sanitation drains, thereby impinging on the overall quality of life in the city. Under the business as usual scenario, prediction analysis for the year 2050 show that built up area will consume almost all of the city area (73.21%) with forest significantly reduced to patches making up only about 16% of the city. These findings beg for an urgent need to implement effective planning specially to protect the existing forest and water resources from further degradation.